2021
DOI: 10.21608/ejchem.2021.62916.3350
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological activity of a new class of enaminonitrile pyrazole

Abstract: The present work illustrates the treatment of 5-amino-1,3-diphenyl-1H-pyrazole-4-carbonitrile (1) with maleic, phthalic anhydrides, acetyl chloride, and benzene sulfonyl chloride to afford the pyrazole derivatives 2-5. The treatment of pyrazole derivative 1 with some active methylene reagents namely: malononitrile, cyanoacetamide, ethyl acetoacetate afforded the pyrazolopyridine 6-9. Reaction of compound 1 with acetic anhydride gave the pyrazolopyrimidinone 10, which was allowed to react with P2S5 and POCl3 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…In this study, designing and synthesizing enamino pyrazole derivative was reported as starting material via one-pot multicomponent reaction using microwave and grinding techniques. On the other hand, the reactions were pressed using thermal method according to literature method [ 43 , 44 ]. Comparison between the percentage yields and consumed times, which resulting from the two techniques were performed.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, designing and synthesizing enamino pyrazole derivative was reported as starting material via one-pot multicomponent reaction using microwave and grinding techniques. On the other hand, the reactions were pressed using thermal method according to literature method [ 43 , 44 ]. Comparison between the percentage yields and consumed times, which resulting from the two techniques were performed.…”
Section: Introductionmentioning
confidence: 99%
“…So now, this green synthesis type is considered a significant technique in heterocyclic chemistry synthesis because of its economy, simplicity, and mild conditions. The ongoing attempts to synthesize novel heterocycle derivatives are motivated by their previously successful uses in industry and biology [31][32][33][34][35][36][37][38][39][40][41][42] . In this study, we report designing and synthesizing a new pyridine-bearing pentose moiety via a one-pot multicomponent reaction using D-glucose [43][44][45] , and also investigate its behavior and reactivity toward some simple and heterocyclic amino derivatives.…”
mentioning
confidence: 99%